Evaluasi Ketertiban Mahasiswa dalam Pelaksanaan Pembayaran Registrasi Uang Kuliah di STPKat Santo Fransiskus Asisi Tahun Akademik 2023/2024 - Claudea Viagta Sisi Apriani (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to evaluate the level of orderliness of students in the implementation of tuition fee registration payments at the St. Fransiskus Assisi Catholic Pastoral College (STPKat) in the 2023/2024 Academic Year. Student orderliness in fulfilling registration payment obligations is an important factor that has an impact on the smoothness of the academic administration process and the operational sustainability of educational institutions. The research method used is descriptive quantitative, with data collection through observation, interviews and analysis of payment documents. The results of the research show the level of student compliance in carrying out tuition registration payments, the factors that influence late payments, as well as the institution's efforts to improve student order. It is hoped that this study can be a reference for the management of STPKat St. Fransiskus Assisi in formulating more effective policies and strategies to increase student discipline in paying tuition registration fees.